Polymorphisms of the MxA and MxB genes are associated with biochemical indices and viral subtypes in Yunnan HCV patients - He, Mengzhu; Liu, Min; Geng, Jiawei; Liu, Li; Huang, Peng; Yue, Ming; Xia, Xueshan; Zhang, A-Mei (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Hepatitis C virus (HCV) infection was the primary reason causing critical hepatic Q7 diseases. Although direct-acting antiviral agents (DAA) were widely used in clinics, anti-drug mutation, the outcome of patients with different viral subtypes, and recurrence suggested that HCV pathogenic mechanism should be studied further. HCV infection, replication, and outcome were influenced by the IFNL4 and itsdownstream genes (MxA and MxB). However, whether genetic polymorphisms of these genes played necessary roles required verification in the Yunnan population. Methods and Results After analyzing the genotypes and allele frequencies of seven single nucleotide polymorphisms (SNP), we found the association between the genotype and allele frequencies of rs11322783 in the IFNL4 gene and HCV infection in Yunnan population. Furthermore, the genetic polymorphisms of the MxA and MxB genescould influence liver function of HCV patients. The indirect bilirubin (IBIL) and albumin (ALB) levels showed significant differences among HCV patients, who carried various genotypes. The IBIL levels were associated with genotypes of rs17000900 (P= 0.025) and rs2071430 (P= 0.037) in the MxA gene, and ALB levels were associated with genotypes of rs2838029 (P= 0.010) in the MxB gene. Similarly, the genotypes of SNPs also showed significant difference in patients infected with subtype 3a (P=0.035) and 2a (P=0.034). However, no association was identified between expression level and SNPs of the MxA and MxB genes. Furthermore, HCV subtype 3b was found to be the predominantly epidemic strain in Yunnan Province. Conclusion In conclusion, the association between biochemical indices/HCV subtypes and SNPs in the MxA and MxB genes was identified in Yunnan HCV population.